Metal-Free C60-Doped Mesoporous Carbon Nitride Drives Red-Light Photocatalysis - Wang, Peng (Langmuir : the ACS journal of surfaces and colloids, 2024)
The pursuit of novel strategies for synthesizing high-performance nanostructures of graphitic carbon nitride (g-C3N4) has garnered increasing scholarly attention in the field of photocatalysis. Herein, we have successfully designed a metal-free photocatalyst by integrating mesoporous carbon nitride (mpg-C3N4) and C60 through a straightforward and innovative method, marking the first instance of such an achievement. Under red light, the C60/mpg-C3N4 composite exhibited a significantly accelerated rhodamine B (RhB) photodecomposition rate, surpassing bulk g-C3N4 by more than 25.8 times and outperforming pure mpg-C3N4 by 7.8 times. The synergistic effect of C60 and the mesoporous structure significantly enhanced the photocatalytic performance of g-C3N4 by adjusting its electronic structure, broadening the light absorption range, increasing the active sites, and reducing the recombination of photogenerated carriers. This work presents a promising avenue for harnessing a metal-free, stable, efficient photocatalyst driven by red light, with potential for enhancing solar energy utilization in environmental remediation